Analgesic drug use in patients with STEMI: Current perspectives and challenges - Chen, Huaigang; Wang, Hong; Li, Bin; Hong, Lang; Kuang, Maobin; Yang, Liu (Frontiers in Medicine, 2023)
Abstract Therapy for patients with ST-elevation myocardial infarction (STEMI) has been a controversial topic since the introduction of thrombolytic agents in the 1980s. The use of morphine, fentanyl and lidocaine has increased substantially during this period. However, there is still limited evidence on their advantages and limitations. In this review, the clinical application, as well as future considerations of morphine, fentanyl and lidocaine in patients with ST segment elevation myocardial infarction were discussed. Keywords: STEMI; P2Y12 receptor antagonists; Morphine; Analgesic; Lidocaine